Enhanced superconductivity with possible re-appearance of charge density wave states in polycrystalline Cu1-xAgxIr2Te4 alloys. (April 2022) - Boubeche, Mebrouka; Zeng, Lingyong; Hu, Xunwu; Guo, Shu; He, Yiyi; Yu, Peifeng; Huang, Yanhao; Zhang, Chao; Luo, Shaojuan; Yao, Dao-Xin; Luo, Huixia
Abstract: In this study, we determined the effect of doping with the noble metal Ag on CuIr2 Te4 superconductors. Based on the resistivity, magnetization, and heat capacity, we explored the changes in the superconductivity (SC) and charge density wave (CDW) for Cu1- x Ag x Ir2 Te4 (0 ≤  x  ≤ 1) as a function of isoelectric substitution (Cu/Ag). We assessed a complete set of competing states from suppressed CDW in the low doping region to superconductor in the middle doping region and re-entrant CDW in the high doping region, thereby obtaining an electronic phase diagram, where the superconducting dome was near bipartite CDW regions with a maximum superconducting temperature ( T c ) of about 2.93 K at an Ag doping level of 12%. The lower H c 1 and upper H c 2 critical magnetic fields were determined for some representative samples in the Cu1- x Ag x Ir2 Te4 series based on magnetization and resistivity measurements, respectively. We showed that H c 1 decreased whereas H c 2 increased as the doping content increased. The specific heat anomalies at the superconducting transitions Δ C el / γT c for representative samples comprising Cu0.92 Ag0.08 Ir2 Te4, Cu0.88 Ag0.12 Ir2 Te4, and Cu0.85 Ag0.15 Ir2 Te4 were approximately 1.40, 1.44, and 1.42, respectively, which are all near the Bardeen-Cooper-Schrieffer (BCS) value of 1.43 and they indicate bulk SC in these compounds. Highlights: Series of new Cu1- x Ag x Ir2 Te4 superconductors investigated. Dome-like superconductivity established. Possible re-appearance of charge density wave states observed.